Material Properties Influencing the Charge Decay of Electret Filters and their Impact on Filtration Performance - Lee, Jinwook (Polymers (Basel), 2020)
Electret filters as opposed to mechanical filters display the enhanced ability to capture airborne particles with the electrostatic attraction. However, the environmental aging during shelf-life or use may cancel its benefit by dissipating the charges. This work investigates the polymeric attributes influencing the charge decay and the electrostatic filtration of electret filters, employing polymers with different dielectric constants (ε(r)) and wettability. As accelerated aging, high temperature (120 °C) or high humidity (25 °C, 90% RH) was applied to the electret filters for 48 h. For the humidity aging, wetting property of material was a critical factor affecting the charge decay and the filtration performance, as the absorbed water increases the electrical conductivity. For the thermal aging, the material with the highest ε(r) deteriorated the electric potential and the filtration performance by the largest extent, due to the lower band gap energy for charge transfer. The results of this study implicate that ε(r) and wettability are important material parameters influencing the electric conductivity and chain mobility, and they can be used as convenient predictors for charge retention capacity affecting the robust electrostatic filtration performance.